Baryon asymmetry and the mass of proton - Bukalov, Aleksandr (Physics of Consciousness and Life, Cosmology and Astrophysics, 2013)
There are obtained the formulas and the relations describing the value of the baryon asymmetry, the number of baryons in the observable universe, and the mass of the proton. Connection the value of the baryon asymmetry of the mass proton and the high stability of the baryon number follows from the proposed formula. It is shown the nonrandomness of the value of the entropy of the Universe.